Impact of group transdiagnostic cognitive‐behavior therapy for anxiety disorders on comorbid diagnoses: Results from a pragmatic randomized clinical trial in primary care. Issue 7 (18th June 2021) - Norton, Peter J.; Provencher, Martin D.; Kilby, Christopher J.; Roberge, Pasquale
Abstract: Background: Anxiety and depressive disorders are the most common mental illnesses worldwide, with most individuals meeting criteria for more than one diagnosis. Most cognitive‐behavioral therapy (CBT) approaches target only one disorder at a time, resulting in the need to treat comorbid diagnoses sequentially. Transdiagnostic CBT protocols have been developed that simultaneously treat principal and comorbid disorders. Method: The current study reports on a secondary analysis of data from a pragmatic effectiveness randomized trial of group tCBT in comparison to treatment‐as‐usual (TAU) in primary care. Of the trial sample of 231 patients, 191 had at least one comorbid diagnosis of clinical severity at T0. Results: Overall rates of comorbidity decreased over time (82.0% at T0, 45.0% at T1, 45.7% at T3) and those receiving tCBT showed a significantly lower rate of comorbidity at T1 (33.7%) than TAU (55.7%) and at T3 (tCBT: 27.9%, TAU: 60.2%). Comorbid diagnosis severity ratings reduced to a significantly greater extent in tCBT than in TAU. Conclusions: tCBT is effective in promoting remission of and reducing the severity of comorbid diagnoses. Implications for the treatment of whole persons as opposed to specific diagnoses is discussed.